2006
DOI: 10.1021/ar0680015
|View full text |Cite
|
Sign up to set email alerts
|

P-Phos:  A Family of Versatile and Effective Atropisomeric Dipyridylphosphine Ligands in Asymmetric Catalysis

Abstract: This Account outlines our efforts in the design and synthesis of a family of highly effective atropisomeric dipyridylphosphine ligands (P-Phos and its variants) and in the development of their widespread applications in transition-metal-catalyzed asymmetric reactions including hydrogenation, hydrosilylation, and C-C bond formation. Desirable attributes, such as air stability, broad substrate scope, fast rates of reaction, excellent enantioselectivities, low catalyst loading, and mild conditions, make the catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(34 citation statements)
references
References 59 publications
0
34
0
Order By: Relevance
“…[9] According to the recent works by Carretero and coworkers, [10] Fesulphos which contained only planar The development of highly efficient and practical chiral ligands for asymmetric C À C bond formation is a long-standing research interest for many scientists. Previously we showed that chiral diphosphine ligands P-Phos [11] with heteroaromatic scaffolds are excellent ligands for asymmetric hydrogenations [12] as well as some C À C bond formation reactions. [13] Notably, these ligands are air-stable compared to the analogous BINAP ligand.…”
Section: Introductionmentioning
confidence: 99%
“…[9] According to the recent works by Carretero and coworkers, [10] Fesulphos which contained only planar The development of highly efficient and practical chiral ligands for asymmetric C À C bond formation is a long-standing research interest for many scientists. Previously we showed that chiral diphosphine ligands P-Phos [11] with heteroaromatic scaffolds are excellent ligands for asymmetric hydrogenations [12] as well as some C À C bond formation reactions. [13] Notably, these ligands are air-stable compared to the analogous BINAP ligand.…”
Section: Introductionmentioning
confidence: 99%
“…The rhodium(I) catalyst formed in situ from [Rh(COD)OH] 2 and Xyl-P-Phos promoted S N 2 allylic substitution with a variety of arylboronic acids with up to 92% ee and >20:1 regioselectivity. 17 2 12 mol % (S)-1 20 mol % AgBF 4 (10)…”
Section: Hydrosilylation Of Ketonesmentioning
confidence: 99%
“…Pyridyl diphosphines have been shown to display various coordination modes: they serve as useful building blocks for di-and polynuclear compounds (MOFs) and have catalytic applications. 4,5 It has been shown recently that secondary diphosphines are excellent precursors for 14-, 16-, 18-, and 20-membered macrocycles. [6][7][8] Here, we present the synthesis of novel pyridyl substituted P-H-diphosphines 1-3 by the reaction of primary pyridyl phosphine with 1,3-dichloropropane, 1,4-dichlorobutane, and 1,5-dichloropentane in potassium hydroxide (KOH)/dimethyl sulfoxide (DMSO) medium in moderate (in the case of 2) or good (in the case of 1 and 3) yields (Scheme 1).…”
Section: Synthesis Of Bis(2-pyridylphosphino)alkanes In Superbasic Mementioning
confidence: 99%